Emotional intelligence and stress and their relationship with breastfeeding self-efficacy in mothers of premature infants - Mohammad Arshadi Bostanabad; Mina Hosseinzadeh; Zahra Molazemi; Hossein Namdar Areshtanab (BMC, 2024)
Abstract Background Premature infants need to be hospitalized in the neonatal intensive care unit (NICU) for long periods of time, which can increase anxiety and stress in their mothers. Additionally, the breastfeeding rate is lower among preterm infants. This study aimed to determine stress levels and emotional intelligence in mothers of preterm infants and their relationship with breastfeeding self-efficacy. Methods This descriptive-correlational study was performed with a convenience sampling of 210 mothers of premature infants admitted to the neonatal intensive care unit in Tabriz, Iran in 2021. Data collection tools included socio-demographic checklist, perceived stress scale (PSS14), Dennis' breastfeeding self-efficacy scale, and the Schering emotional intelligence questionnaire. Data were analyzed using SPSS software version 16 via descriptive and inferential statistics (Pearson correlation and one-way ANOVA and modified general linear model). Results Study findings demonstrated that most of the mothers had low stress (75.2%) and high breastfeeding self-efficacy (61.9%). The mean (SD) of emotional intelligence of the participants was 88.18 (16.60), ranging from 33 to 165. The results of the general linear model by modifying the demographic characteristics showed that the variables of emotional intelligence (B = 0.23, P = 0.03), stress (B=-0.56, P = 0.01), gestational age (B = 2.81, P < 0.001) and number of deliveries (B = 9.41, P < 0.001) were predictors of breastfeeding self-efficacy. Conclusion The findings showed that mothers of preterm infants had low emotional intelligence, and the majority of them had low perceived stress and high breastfeeding self-efficacy. Findings highlight the importance of addressing maternal stress and enhancing emotional intelligence to promote successful breastfeeding in mothers of preterm infants. Healthcare providers and managers are encouraged to offer support and educational programs to mothers of preterm infants, aiming to enhance their emotional intelligence. Further research and interventions focusing on these factors are warranted to improve the overall well-being of both mothers and infants in the neonatal intensive care unit.